MUTUALITAS KELUARGA KRISTEN MENURUT KOLOSE 3:18-21 (THE QUALITY OF THE CHRISTIAN FAMILY ACCORDING TO COLOSSIANS 3:18-21) - Handry David Rumimpunu; Sutrisno Sutrisno; Marthin Steven Lumingkewas (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2020)
Modern civilization with its industrialization has brought many changes to Christian family life, where modernization also means a shift from an agrarian society to an industrial society. This development brings about changes that have a direct impact on family life, both in the patterns and roles of the Christian family, as well as in attitudes and views of the values that are the foundation of family life. The article aims to discover the meaning of the mutuality of the Christian family based on Colossians 3: 18-21. In achieving these objectives, this study uses descriptive qualitative methods. The conclusion is that the formation of a family on earth began when Allah created and blessed husband, wife, and child as a complete and perfect family in God's sight with love, obedience, respect, and responsibility. Peradaban modern dengan industrialisasinya telah membawa banyak perubahan bagi kehidupan keluarga Kristen, dimana modernisasi juga berarti pergeseran dari masyarakat agraris ke masyarakat industri. Perkembangan ini membawa perubahan yang mempunyai dampak langsung bagi kehidupan keluarga, baik dalam pola dan peranan keluarga Kristen, maupun dalam sikap dan pandangan terhadap nilai-nilai yang menjadi sendi kehidupan keluarga. Artikel memiliki maksud untuk menemukan makna mutualitas keluarga Kristen berdasarkan Kolose 3:18-21. Dalam mencapai tujuan tersebut penelitian ini menggunakan metode kualitatif deskriptif. Hasilnya adalah pembentukan keluarga di muka bumi dimulai ketika Allah menciptakan dan memberkati suami, istri, dan anak sebagai keluarga yang lengkap dan sempurna dalam pandangan Allah dengan kasih, ketaatan, menghormati, dan bertanggung jawab.